Effects of Age, Vitamin D3 and Fructooligosaccharide on Correlation of Different Bone Parameters in Broiler Chickens - Regassa, A.; Kim , W.K. (International Journal of Poultry Science, 2014)
Effects of age, vitamin D3 (VitD3) and Fructooligosaccharide (FOS) on the correlations of bone parameters were examined in broiler chickens. A total of 36 d-old male chicks were placed in battery brooders and fed a corn/soybean starter diet for 7 days and were randomly assigned to 12 pens each containing 3 birds. In group 1, birds were fed a corn/soybean starter diet and sacrificed on d 14 and 21. In groups 2 and 3, birds were fed a starter diet +250 μg VitD3/kg of diet and 4% FOS/kg of diet for 21 d, respectively. Birds were sacrificed to collect femur bones for measurement of bone parameters. Data were analyzed using Spearman’s correlation analysis. Total mineral density (BMD) and trabecular density (r14 = 0.99, p14 = 0.0001; r21 = 0.90, p21 = 0.0001), total bone area and trabecular area (r14 = 0.99, p14 = 0.0001; r21 = 1.00, p21 < 0.0001) and trabecular mineral content and cortical mineral content (r14 = 0.99, p14 < 0.0001; r21 = 0.96, p21< 0.0001) were strongly correlated both on d 14 and 21. In birds treated with VitD3 and FOS, bone mineral content (BMC) and cortical bone mineral content (r = 0.95, p < 0.0001) and BMD and trabecular mineral content (r = 0.92, p = 0.0004), were strongly correlated but most of the parameters were moderately or weakly correlated. In conclusion, results of this study show that age of birds, VitD3 and FOS treatments influence the relationships among the bone parameters.